Prenatal phenotype analysis and mutation identification of a fetus with meckel gruber syndrome - Moreno-Leon, Laura; Quezada-Ramirez, Marco A.; Bilsbury, Evan; Kiss, Courtney; Guerin, Andrea; Khanna, Hemant (Frontiers in Genetics, 2022)
Ciliopathies are a class of inherited severe human disorders that occur due to defective formation or function of cilia. The RPGRIP1L (retinitis pigmentosa GTPase regulator- interacting protein1-like) gene encodes for a ciliary protein involved in regulating cilia formation and function. Mutations in RPGRIP1L cause ciliopathies associated with severe embryonic defects, such as Meckel-Gruber Syndrome (MKS). Here we report RPGRIP1L mutation analysis in a family diagnosed with MKS. The clinical manifestations of the fetus included thoraco-lumbar open neural tube defect with associated Chiari type II malformation and hydrocephalus, bilateral club feet, and single right kidney/ureter. Analysis of the parental DNA samples revealed that the father carried a previously reported mutation R1236C/+ whereas the mother had a novel splice site mutation IVS6+1 G>A/+ in RPGRIP1L. The splice site mutation resulted in the exclusion of in-frame exon 6 of RPGRIP1L (RPGRIP1L-∆Ex6) but expressed a stable protein in fibroblasts derived from the parents’ skin biopsies. The GFP-RPGRIP1L-∆Ex6 mutant protein exhibited relatively reduced ciliary localization in transiently-transfected cultured RPE-1 cells. Taken together, this study identifies a novel RPGRIP1L variant RPGRIP1L-∆Ex6, which in combination with RPGRIP1L-R1236C is associated with MKS. We also suggest that the deletion of exon 6 of RPGRIP1L leads to reduced ciliary localization of RPGRIP1L, indicating a plausible mechanism of associated disease.